Hidden debates - Hermes, Joke (Javnost (Ljubljana), 2006)
This article proposes that paying attention to popular cultural practice will benefit "cultural citizenship" and, in turn, the vitality of the public sphere. Although popular culture in Habermassian terms does not fully qualify as a lifeworld domain, the enthusiasm of its users is a strong point to its advantage. Otherwise "ordinary people" hardly participate in public life, which foregrounds them as (emotional) witnesses rather than as experts or persons holding a view or an (interesting) opinion. As debate resulting from popular culture use tends to be among fans, neighbours or co-workers and is inpoint of fact "hidden," a further step would be needed to use the underlyingissues and points of view debated in everyday life for public use. Internet communication shows that this is well possible. Indeed, the public-private and the fiction-non fiction boundaries are blurring, and citizenship is practiced in many places. Qualitative audience research could be a key force in reinvigorating the public sphere. By involving audience members themselves and following their cue or by using peer-to-peer formats, it could develop into "civic research" in much the same manner as civic journalism.
Keywords: javna sfera; javnost; popularna kultura; communication; komuniciranje; množične komunikacije; internet